Beyond Adoption: Stakeholders' Roles in the Diffusion of Sustainable Supply Chain Management - A Case Study Analysis - Mourtaka, Samah (ExcelingTech, 2025)
This study examines the wide-ranging impact of companies' decisions to adopt Sustainable Supply Chain Management (SSCM) practices on their stakeholders and the subsequent diffusion of these practices across the stakeholder network. Drawing on game theory, the research investigates how stakeholder interactions and reciprocal influences contribute to the spread of sustainable practices within and beyond organizational boundaries. Through a qualitative, multiple case study approach involving three major Moroccan companies, the study employs triangulation and cross-case analysis to uncover the complex dynamics underlying SSCM implementation. The findings reveal that stakeholder relationships evolve into iterative, strategic interactions that not only reinforce sustainability adoption within individual firms but also catalyse broader diffusion across the supply chain ecosystem.The study contributes to SSCM literature by: (1) clarifying the mechanisms grounded in gametheoretical principles-that underpin sustainability diffusion, and (2) offering rare empirical insights from an emerging market context. By linking SSCM adoption to strategic stakeholder engagement, the research underscores its transformative potential for sustainable development. These insights are particularly valuable for policymakers, practitioners, and scholars seeking to leverage SSCM for broader societal impact.